Hubungan Antara Identitas Diri Dan Perkembangan Kepercayaan Eksistensial Dengan Tingkat Perkembangan Penalaran Moral Remaja Di Kodya Padang - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT The object of this research is to study the relationship between self-identity and faith development to moral reasoning of adolescent, and even to study the different level of moral reasoning development between early adolescence and late adolescence. The subject involved 419 adolescents